2021
DOI: 10.21511/ppm.19(2).2021.13
|View full text |Cite
|
Sign up to set email alerts
|

Strategic human resource management practices and human capital development: The role of employee commitment

Abstract: This paper studied the influence of strategic human resource management on human capital development through the mediation of employee commitment. A descriptive cross-sectional study design was used to collect data from 514 participants (medical staff) from five hospitals in northern Jordan. The hospitals involved were from different sectors, including governmental, private, and university hospitals. Several analysis methods were used in the study: Confirmatory Factor Analysis (CFA), discriminant validity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…Authors emphasize that it is important for the health care workforce not only to develop individual knowledge, but also the internalization of tacit knowledge should be practiced. Human capital should be managed through the practice of strategic human resource management, by investing more in human capital through formal education and training (Alolayyan, Alyahya, & Omari, 2021). Second, a combination of skills appropriate to the specifics of the job is important not only for clinicians, but also for managers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors emphasize that it is important for the health care workforce not only to develop individual knowledge, but also the internalization of tacit knowledge should be practiced. Human capital should be managed through the practice of strategic human resource management, by investing more in human capital through formal education and training (Alolayyan, Alyahya, & Omari, 2021). Second, a combination of skills appropriate to the specifics of the job is important not only for clinicians, but also for managers.…”
Section: Discussionmentioning
confidence: 99%
“…Outputs can be expressed not only in terms of the quality and safety of clinicians' work but also in the spirit and cohesiveness of the employees (McMahon, 2017) as well as improved workforce commitment (Alolayyan et al, 2021). The more healthcare managers invest in meaningful formal training and organizational programs to enhance employees' skills and competencies related to organizational strategic goals, the less likely employees will leave their organizations or look for another opportunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,33 Employees interpret good HR practices positively and reciprocate with high OC. 3 Examining the impact of HR practices on OC requires a closer look at HRM elements. Because of their unique characters, each factor should be investigated separately because it may have a different impact on OC.…”
Section: Introductionmentioning
confidence: 99%
“…22,26,28,30 However, several studies also suggested that training may not significantly impact OC; hence it's worth investigating. 3,15,31 Performance appraisal and evaluation. Employee performance is assessed based on several factors, and if performance evaluations are poorly designed and executed, employees will fail to recognise the value of such exercises.…”
Section: Introductionmentioning
confidence: 99%